2001
DOI: 10.1067/mva.2001.116804
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and suppression of intimal hyperplasia of vascular grafts with a distal arteriovenous fistula in a rat model

Abstract: A small animal experimental model of an arterial bypass graft can enable the evaluation of a variety of factors that influence graft patency. Increased blood flow velocity and shear stress induced by a dAVF are associated with a decrease in intimal and medial areas, which may reflect changes in cell proliferation, apoptosis, migration, or matrix deposition. Deposition of vWF was also found both in the endothelium and throughout the hyperplastic intima. These findings suggest that the hemodynamic and morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
2
28
1
Order By: Relevance
“…In 1969, Caro et al 11 published their observations that atherosclerosis develops in areas of low wall shear. After they reported that arterial curvature is commonly helical, resulting in swirling flow and elevation of wall shear, 9 many important observations have been made: (1) IH also develops at areas of low wall shear and conversely is less likely at areas of elevated wall shear 10,12,[22][23][24] ; (2) straight stents reduce the natural helical curvature of an artery; and (3) individual stent designs affect the volume of IH that develops, which is not solely dependent on the degree of injury. [25][26][27][28] Swirling flow induced by a helix has high wall shear [9][10][11][12][13][14] and when generated by a helical dialysis graft reduces the IH when compared with a conventional graft.…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, Caro et al 11 published their observations that atherosclerosis develops in areas of low wall shear. After they reported that arterial curvature is commonly helical, resulting in swirling flow and elevation of wall shear, 9 many important observations have been made: (1) IH also develops at areas of low wall shear and conversely is less likely at areas of elevated wall shear 10,12,[22][23][24] ; (2) straight stents reduce the natural helical curvature of an artery; and (3) individual stent designs affect the volume of IH that develops, which is not solely dependent on the degree of injury. [25][26][27][28] Swirling flow induced by a helix has high wall shear [9][10][11][12][13][14] and when generated by a helical dialysis graft reduces the IH when compared with a conventional graft.…”
Section: Discussionmentioning
confidence: 99%
“…20e27 Recent experiments suggest that the creation of a fistula may suppress intimal hyperplasia by release of active cellular molecules. 28,29 Others have also shown enhanced flow through flaps at micro and macro levels. 30e34 An intriguing finding is the need for an arteriovenous loop shunt to enable angiogenic capillary budding in experimental bone regeneration in reactors.…”
Section: Discussionmentioning
confidence: 96%
“…24 In addition, high blood flow inhibits intimal hyperplasia after arterial injury. 25,26 After 4 days, medial SMC proliferation reaches a peak in both rodent and primate models of injury, and SMCs begin to migrate to the intima. PDGF clearly plays a major stimulatory role for SMC migration in both rodents 27 and primates.…”
Section: Mechanisms Of Vascular Hyperplasia and Hypertrophymentioning
confidence: 99%